PENERAPAN METODE AHP (ANALYTICAL HIERARCHY PROCESS) UNTUK PEMILIHAN SUPPLIER SUKU CADANG DI PLTD BITUNG - Sean Imanuel Pebakirang; Agung Sutrisno; Johan S C Neyland (Fakultas Teknik Jurusan Teknik Mesin Universitas Sam Ratulangi, 2017)
In choosing supplier supplying goods to companies, there are many considerations in making decision to choice appropriate suppliers. In order to make an appropriate decision there is a need to choice suitable suppliers. In this study, the AHP is used to choose supplier using case example from electricity generating companies. Based on the research results by applying the method of AHP, then the value of the highest weight is the value of quantity attribute (1.0610), then the weight of the price (0.9942), availability of materials (0.9893), quality (0.9888), and continuity attribute (0.8419). As the alternative preferences, which gained the highest weightis in the followings; PT. Kawanua Rekacipta (2.4174), CV. Karya Citra Abadi (1.2595), dan CV. Diva Multi Prima (1.2140). . Keywords : AHP, Supplier, Criteria, Spare Part, Alternative